Does Other Comprehensive Income Volatility Influence Credit Risk and the Cost of Debt? - Bao, May Xiaoyan; Billett, Matthew T.; Smith, David B.; Unlu, Emre (Contemporary Accounting Research, 2020)
ABSTRACT We examine the usefulness of other comprehensive income (OCI) to debt investors in nonfinancial companies. Motivated by Merton's (1974) real options framework, we construct a measure of incremental OCI volatility, designed to capture the effect of OCI on overall firm asset volatility, which is a primary driver of credit risk in Merton's (1974) model. We find that the volatility of incremental OCI influences the likelihood of default, credit ratings, and the cost of debt. Overall, our evidence suggests that creditors use information from OCI in their assessment of firm credit risk and in pricing debt contracts.